The Economics of Full Reserve Banking: Recent Developments and Critiques - Raubenheimer, Grace (School of Economics, 2023)
Following the Great Depression (1929-1933) and the Great Financial Crisis (2007-2009) a call to reform the banking sector arose. There was evidence that the banking sector, and their poor decisions, was a principal cause of two of the biggest economic crises. One such reform was the Full Reserve Banking (FRB) proposal, originating in the 1930s with the Chicago Plan. The Plan proposed forcing banks to hold 100% of deposits as reserves to prevent another financial crisis. Full Reserve Banking is the subject of this dissertation. The Chicago Plan and two modern full reserve proposals are discussed. The workings of the banking sector and the role of central bank are present to provide context and contrast to the Full Reserve Banking reforms. The following section discusses the Great Financial Crisis and illustrates the need for reform in the banking sector. Full Reserve Banking is defined and three proposals for FRB are presented, the Chicago Plan of the 1930s, the Sovereign Money proposal from 2012 and the Narrow Banking plan of 2009. Some critiques of FRB are discussed. These critiques are provided alongside a discussion of whether Full Reserve Banking is a viable option. The critiques that are raised do focus on the technical economics of the FRB proposals, rather the discussion presented the undesired consequences of FRB and the viability of implementing FRB is evaluated.